Human Harmony with Nature in Ahmad Tohari's Novels - Trianton, Teguh (International Proceedings of Nusantara Raya, 2024)
Human relations with the environment and nature are influenced by the values ​​of cultural wisdom regarded as the way of life within a community entity. These values ​​ are stored in various artifacts or forms, such as literary works. The values ​​of local wisdom in the context of Banyumas culture are recorded in the novels written by Ahmad Tohari (AT). Therefore, this study aims to determine the concept of harmony in the relationship between mankind and nature in the cultural treasures of Banyumas. This is a qualitative and descriptive research analyzed using the content analysis method. The theory used is literary anthropology, and the study was conducted as a form of conservation of the values ​​of Banyumas cultural wisdom. The result showed that the Banyumas people have a human harmony with nature that is simultaneously based on spiritual values. First, they are of the view that man must submit to the forces of nature. This philosophy is applied when nature shows its power surpasses humans'. Second, they try to conquer nature for the sake of survival and fulfillment of life's needs. Third, in terms of the conquest of nature, they consider aspects of the harmony and balance of the ecosystem.